Management Control Systems and Its Effect on Performance - Agung Praptapa; Mohd Azlan B Yahya; Norfaiezah Binti Sawandi (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
This paper discusses how Management Control Systems is used to control performance in local government owned companies in Indonesia. Performance becomes important and unique in local government owned companies since those companies are not only targeted by profit but they also have responsibilities for social function. This study focuses on performance control in water supply companies as typical local government owned company in Indonesia. Balance Scorecard is chosen as the performance measurement tool in all water supply companies in Indonesia. This research applies quantitative research in order to analyze cause effect relationship between variables by using Multiple Regression Analysis. Data is collected through survey by using questionnaires. The respondents were the managerial team and employees of local government owned companies in Indonesia. The results show that four perspectives of Balance Scorecard are modified into four types of performance i.e. financial, service, operational, and human resource performance. This performance measurement is used to control people in achieving targeted performance. Moreover, this performance measurement becomes an important part of management control systems. This research also discovers that management control systems is effective to influence performance, even when some interventions exist.